Carbon nanotube conductive paste and preparation method and stability evaluation method thereof

CN119601611APending Publication Date: 2025-03-11SUZHOU SYNMINWAY NANO TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411409014.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-03-11

Smart Images

  • Figure BDA0005077475450000081
    Figure BDA0005077475450000081
  • Figure BDA0005077475450000091
    Figure BDA0005077475450000091
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and discloses carbon nanotube conductive paste and a preparation method and a stability evaluation method thereof. The invention discloses a carbon nanotube conductive paste, which comprises the following components: a carbon nanotube, an additive, a dispersant, N-methyl pyrrolidone, and a basalt fiber material. The preparation of the conductive slurry comprises the following steps: firstly, mixing and ball-milling the carbon nano tube and the basalt fiber material to obtain a ball-milled material, adding the additive, the dispersing agent and the N-methyl pyrrolidone into the ball-milled material, mixing, and carrying out ultrasonic treatment to obtain the carbon nano tube conductive slurry. In view of the problems of poor fluidity and dispersibility of the existing oil-based carbon nanotube slurry, the invention aims to provide the carbon nanotube conductive slurry and the preparation method and the stability evaluation method thereof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a carbon nanotube conductive slurry and a preparation method and a stability evaluation method thereof. Background Art

[0002] Lithium-ion batteries are a new type of energy storage battery developed after the 1970s, and are widely used due to their high specific energy, low consumption, low self-discharge rate, long cycle life and pollution-free advantages. Carbon nanotubes have excellent conductivity and lithium insertion properties. Due to the short length of carbon nanotubes, the depth and travel of lithium ions when embedded and released are small. When carbon nanotubes are used as negative electrodes, the polarization degree is small when charging and discharging under high current, which is conducive to improving the charge and discharge capacity and current density of lithium-ion batteries, and will also improve the battery's high current charge and discharge and rapid charge and discharge capabilities.

[0003] During the dispersion process of carbon nanotubes, due to the strong van der Waals force between carbon nanotubes, and their huge specific surface area and aspect ratio, they are very easy to form agglomeration or entanglement, which ultimately leads to increased viscosity of the conductive slurry, poor fluidity, poor stability and other problems. At present, there is a gel state in the oil-based carbon nanotube slurry, and the viscosity rebounds quickly, lacks fluidity, poor dispersibility, and mechanical stirring is required before use. Therefore, in order to give full play to the excellent properties of carbon nanotubes and make them widely used, how to evenly and stably disperse carbon nanotubes, reduce the viscosity of the conductive slurry and enhance the stability of the conductive slurry is a key problem that needs to be solved urgently. How to develop a low-viscosity, high-stability oily carbon nanotube slurry and achieve a method for preparing carbon nanotubes with high fluidity, high dispersibility and no sedimentation is an important research direction in this field. Summary of the invention

[0004] In view of the poor fluidity and dispersibility of the current oil-based carbon nanotube slurry, the present invention aims to provide a carbon nanotube conductive slurry and a preparation method and stability evaluation method thereof.

[0005] The object of the present invention is to provide a carbon nanotube conductive paste, which comprises the following components by mass: 100-150 parts of carbon nanotubes, 4-10 parts of additives, 3-8 parts of dispersants, and 700-900 parts of N-methylpyrrolidone.

[0006] Furthermore, the additive is a combination of urea and potassium dihydrogen phosphate in a mass ratio of 3 to 6:2. The doping of N and P elements can effectively improve the interface stability of the solid content of the carbon nanotube slurry and reduce the viscosity of the slurry; it can also increase the defect sites, optimize the conductive channel, and improve the conductive performance and durability.

[0007] Furthermore, the components of the conductive slurry include, according to the above mass percentages, 15 to 25 parts of basalt fiber material; the basalt fiber material is basalt fiber modified by a silane coupling agent. The basalt fiber modified by a silane coupling agent is then added therein, and contains hydroxyl, carbonyl or carboxyl groups, etc., which can well improve the interface performance; and the presence of cations on the surface facilitates the increase of the surface potential, so that the surface carries a positive charge, which is conducive to making a positive electrode material for a battery.

[0008] Furthermore, the preparation of the basalt fiber material is as follows: basalt fiber and anhydrous ethanol solution are mixed in a mass ratio of 1:15-30, mixed and stirred at 30-45° C. for 2-5 hours, filtered and dried; the anhydrous ethanol solution contains 2-5% by mass of silane coupling agent KH550; the particle size of the basalt fiber is 100-150 nm.

[0009] Furthermore, the dispersant is at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and dodecyl betaine.

[0010] A method for preparing a carbon nanotube conductive slurry, the method comprising the following steps:

[0011] (1) Taking, by weight, 100 to 150 parts of carbon nanotubes, 4 to 10 parts of additives, 3 to 8 parts of dispersants, 15 to 25 parts of basalt fiber materials, and 700 to 900 parts of N-methylpyrrolidone;

[0012] (2) First, carbon nanotubes and basalt fiber materials are mixed and ball-milled to obtain ball mill material, and additives, dispersants, and N-methylpyrrolidone are added to the ball mill material, and then ultrasonic treatment is performed to obtain carbon nanotube conductive slurry.

[0013] Furthermore, the ball milling process in step (2) is as follows: using anhydrous ethanol that is 50-70% of the mass of the ball mill material as the ball milling medium, ball milling in a clockwise direction for 6-15 minutes, standing for 1-3 minutes, and then ball milling in a counterclockwise direction for 6-15 minutes as one ball milling cycle, and performing 20-30 ball milling cycles.

[0014] Furthermore, in step (2), the power of the ultrasonic treatment is 300-500W, and the treatment time is 2-8min.

[0015] The evaluation method comprises the following steps: tracking and recording the upper layer solid content and viscosity data of the conductive paste for a period of 3 to 5 months, setting up a control group and a marketed similar product group for synchronous tracking and recording, and judging the stability of the obtained data with the help of a curve chart.

[0016] Compared with the prior art, the advantages of the present invention are:

[0017] The present invention adopts carbon nanotubes as the main raw material, and mixes additives containing nitrogen and phosphorus elements and activated basalt fiber materials. The solid content is evenly refined by clockwise and counterclockwise ball milling, which can effectively destroy the agglomeration or entanglement of carbon nanotubes, facilitate the improvement of dispersion effect, and improve the conductive channel. And it has been verified by experiments that the obtained conductive slurry has low viscoelasticity, good dispersion stability, and a long battery cycle life. DETAILED DESCRIPTION

[0018] The following provides a specific implementation of a carbon nanotube conductive paste and a preparation method and a stability evaluation method of the present invention. It is necessary to point out that the following examples are only used to explain the present invention in more detail, rather than narrowing the scope of protection of the present invention. After reading the present invention, improvements and adjustments made by professionals in this technical field without departing from the concept of the present invention are within the scope of protection required by the present invention.

[0019] Example 1

[0020] A carbon nanotube conductive slurry comprises the following components by weight: 100 parts of carbon nanotubes, 4 parts of additives, 3 parts of dispersants, 15 parts of basalt fiber materials, and 700 parts of N-methylpyrrolidone.

[0021] Wherein, the additive is a combination of urea and potassium dihydrogen phosphate in a mass ratio of 3 to 6:2.

[0022] Wherein, the basalt fiber material is basalt fiber modified by a silane coupling agent.

[0023] The preparation of the basalt fiber material is as follows: basalt fiber and anhydrous ethanol solution are mixed in a mass ratio of 1:15, stirred at 35° C. for 2 hours, filtered and dried; the anhydrous ethanol solution contains 3% by mass of silane coupling agent KH550; the particle size of the basalt fiber is 100-150 nm.

[0024] Wherein, the dispersant is at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and dodecyl betaine.

[0025] A method for preparing a carbon nanotube conductive slurry, the method comprising the following steps:

[0026] (1) Take 100 parts of carbon nanotubes, 4 parts of additives, 3 parts of dispersants, 15 parts of basalt fiber materials, and 700 parts of N-methylpyrrolidone by weight;

[0027] (2) First, carbon nanotubes and basalt fiber materials are mixed and ball-milled to obtain ball mill material, and additives, dispersants, and N-methylpyrrolidone are added to the ball mill material, and then ultrasonic treatment is performed to obtain carbon nanotube conductive slurry.

[0028] The ball milling process in step (2) is as follows: using anhydrous ethanol that is 50% of the mass of the ball mill material as the ball milling medium, ball milling in a clockwise direction for 10 minutes, standing for 2 minutes, and then ball milling in a counterclockwise direction for 10 minutes as one ball milling cycle, and performing 25 ball milling cycles.

[0029] Wherein, the power of the ultrasonic treatment in step (2) is 400W and the treatment time is 5min.

[0030] The evaluation method includes the following steps: tracking and recording the upper layer solid content and viscosity data of the conductive paste for a period of 3 to 5 months, setting up a control group and a commercially available similar product group for simultaneous tracking and recording, and using the obtained data to judge stability with the help of a curve chart.

[0031] Example 2

[0032] A carbon nanotube conductive slurry comprises the following components by weight: 120 parts of carbon nanotubes, 6 parts of additives, 6 parts of dispersants, 20 parts of basalt fiber materials, and 800 parts of N-methylpyrrolidone.

[0033] Furthermore, the additive is a combination of urea and potassium dihydrogen phosphate in a mass ratio of 5:2.

[0034] Furthermore, the basalt fiber material is basalt fiber modified by a silane coupling agent.

[0035] Furthermore, the preparation of the basalt fiber material: basalt fiber and anhydrous ethanol solution are mixed in a mass ratio of 1:20, mixed and stirred at 40° C. for 3 hours, filtered and dried; the anhydrous ethanol solution contains 3% by mass of silane coupling agent KH550; the particle size of the basalt fiber is 100-150 nm.

[0036] Furthermore, the dispersant is at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and dodecyl betaine.

[0037] A method for preparing a carbon nanotube conductive slurry, the preparation method comprising the following steps:

[0038] (1) Take 120 parts of carbon nanotubes, 6 parts of additives, 6 parts of dispersants, 20 parts of basalt fiber materials, and 800 parts of N-methylpyrrolidone by weight;

[0039] (2) First, carbon nanotubes and basalt fiber materials are mixed and ball-milled to obtain ball mill material, and additives, dispersants, and N-methylpyrrolidone are added to the ball mill material, and then ultrasonic treatment is performed to obtain carbon nanotube conductive slurry.

[0040] The ball milling process in step (2) is as follows: using anhydrous ethanol that is 50% of the mass of the ball mill material as the ball milling medium, ball milling in a clockwise direction for 10 minutes, standing for 2 minutes, and then ball milling in a counterclockwise direction for 10 minutes as one ball milling cycle, and performing 25 ball milling cycles.

[0041] Wherein, the power of the ultrasonic treatment in step (2) is 400W and the treatment time is 5min.

[0042] The evaluation method includes the following steps: tracking and recording the upper layer solid content and viscosity data of the conductive paste for a period of 3 to 5 months, setting up a control group and a commercially available similar product group for simultaneous tracking and recording, and using the obtained data to judge stability with the help of a curve chart.

[0043] Example 3

[0044] A carbon nanotube conductive slurry comprises the following components by weight: 150 parts of carbon nanotubes, 10 parts of additives, 8 parts of dispersants, 25 parts of basalt fiber materials, and 900 parts of N-methylpyrrolidone.

[0045] Furthermore, the additive is a combination of urea and potassium dihydrogen phosphate in a mass ratio of 6:2.

[0046] Furthermore, the basalt fiber material is basalt fiber modified by a silane coupling agent.

[0047] Furthermore, the preparation of the basalt fiber material: basalt fiber and anhydrous ethanol solution are mixed in a mass ratio of 1:15-30, mixed and stirred at 45°C for 5 hours, filtered and dried; the anhydrous ethanol solution contains 5% by mass of silane coupling agent KH550; the particle size of the basalt fiber is 100-150nm.

[0048] Furthermore, the dispersant is at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and dodecyl betaine.

[0049] A method for preparing a carbon nanotube conductive slurry, the preparation method comprising the following steps:

[0050] (1) By weight, 150 parts of carbon nanotubes, 10 parts of additives, 8 parts of dispersants, 25 parts of basalt fiber materials, and 900 parts of N-methylpyrrolidone were taken;

[0051] (2) First, carbon nanotubes and basalt fiber materials are mixed and ball-milled to obtain ball mill material, and additives, dispersants, and N-methylpyrrolidone are added to the ball mill material, and then ultrasonic treatment is performed to obtain carbon nanotube conductive slurry.

[0052] The ball milling process in step (2) is as follows: using anhydrous ethanol that is 50% of the mass of the ball mill material as the ball milling medium, ball milling in a clockwise direction for 10 minutes, standing for 2 minutes, and then ball milling in a counterclockwise direction for 10 minutes as one ball milling cycle, and performing 25 ball milling cycles.

[0053] Wherein, the power of the ultrasonic treatment in step (2) is 400W and the treatment time is 5min.

[0054] The evaluation method includes the following steps: tracking and recording the upper layer solid content and viscosity data of the conductive paste for a period of 3 to 5 months, setting up a control group and a commercially available similar product group for simultaneous tracking and recording, and using the obtained data to judge stability with the help of a curve chart.

[0055] Comparative Example 1: It is basically the same as Example 2, except that basalt fiber material is missing.

[0056] Comparative Example 2: It is basically the same as Example 2, except that the additive is missing.

[0057] Comparative Example 3: The same as Example 2, except that the periodic ball milling was replaced by clockwise ball milling only.

[0058] The fluidity and viscosity of the carbon nanotube conductive pastes prepared in Examples 1-3 and Comparative Examples 1-3 were tested, and the cycle performance of the batteries assembled in Examples 1-3 and Comparative Examples 1-3 was tested. The test results are shown in Table 1.

[0059] The fluidity of the conductive paste is tested by visually observing whether the finished conductive paste has fluidity.

[0060] The test method for the viscosity of the conductive paste is: rotation method GB / T10247-2008.

[0061] The test method for the stability of the conductive paste is to judge by tracking and observing the upper layer solid content and viscosity data of the conductive paste within three months.

[0062] The test method for the sedimentation of the conductive paste is to judge by tracking and observing the upper layer solid content and viscosity data of the conductive paste within three months.

[0063] The test method for the battery cycle life is as follows: at room temperature, charge at 0.5C current to a charge termination voltage of 4.3V, then switch to constant voltage charging, stop charging when the charging current drops to 0.02C, leave for 0.5h, discharge at 0.5C current to a discharge termination voltage of 2.5V, leave for 0.5h, and cycle this 100 times.

[0064] Table 1. Performance test results

[0065]

[0066]

[0067] From the above test, it can be seen that the products obtained in Examples 1 to 3 have good performance effects. Comparative Example 2 lacks the main functional component Wuyan fiber material and additives, resulting in a decrease in all properties; Comparative Example 3 is basically the same as Example 2, except that the periodic ball milling is replaced by only clockwise ball milling, resulting in a certain degree of decrease in fluidity and viscosity.

[0068] Note: The above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention; therefore, although this specification has described the present invention in detail with reference to the above embodiments, a person skilled in the art should understand that the present invention can still be modified or replaced by equivalents; and all technical solutions and improvements thereof that do not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A carbon nanotube conductive paste, characterized in that: The conductive paste comprises the following components by weight: 100 to 150 parts of carbon nanotubes, 4 to 10 parts of additives, 3 to 8 parts of dispersants, and 700 to 900 parts of N-methylpyrrolidone.

2. The carbon nanotube conductive paste according to claim 1, characterized in that: The additive is a combination of urea and potassium dihydrogen phosphate in a mass ratio of 3 to 6:

2.

3. The carbon nanotube conductive paste according to claim 1, characterized in that: The components of the conductive paste further include, according to the above mass percentages: 15 to 25 parts of basalt fiber material; the basalt fiber material is basalt fiber modified by a silane coupling agent.

4. The carbon nanotube conductive paste according to claim 3, characterized in that: Preparation of the basalt fiber material: basalt fiber and anhydrous ethanol solution are mixed at a mass ratio of 1:15-30, mixed and stirred at 30-45°C for 2-5h, filtered and dried; the anhydrous ethanol solution contains 2-5% by mass of silane coupling agent KH550; the particle size of the basalt fiber is 100-150nm.

5. The carbon nanotube conductive paste according to claim 1, characterized in that: The dispersant is at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and dodecyl betaine.

6. A method for preparing a carbon nanotube conductive paste according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: (1) Taking, by weight, 100 to 150 parts of carbon nanotubes, 4 to 10 parts of additives, 3 to 8 parts of dispersants, 15 to 25 parts of basalt fiber materials, and 700 to 900 parts of N-methylpyrrolidone; (2) First, carbon nanotubes and basalt fiber materials are mixed and ball-milled to obtain ball mill material, and additives, dispersants, and N-methylpyrrolidone are added to the ball mill material, and then ultrasonic treatment is performed to obtain carbon nanotube conductive slurry.

7. The method for preparing the carbon nanotube conductive paste according to claim 6, characterized in that: The ball milling process in step (2) is as follows: using anhydrous ethanol that accounts for 50-70% of the mass of the ball milling material as the ball milling medium, ball milling in a clockwise direction for 6-15 minutes, standing for 1-3 minutes, and then ball milling in a counterclockwise direction for 6-15 minutes as one ball milling cycle, and performing 20-30 ball milling cycles.

8. The method for preparing carbon nanotube conductive paste according to claim 6, characterized in that: The power of the ultrasonic treatment in step (2) is 300-500W, and the treatment time is 2-8min.

9. A method for evaluating the stability of a carbon nanotube conductive paste according to any one of claims 1 to 5, characterized in that: The evaluation method comprises the following steps: tracking and recording the upper layer solid content and viscosity data of the conductive paste for a period of 3 to 5 months, setting up a control group and a marketed similar product group for synchronous tracking and recording, and judging the stability of the obtained data with the help of a curve chart.